(untitled) (Texas Journal of Engineering and Technology, 2023)
This article discusses the relevance and prospects for the use of thermoelectric power converters as alternative energy sources. Interest in the problem is due to the development of technologies for obtaining modern materials and the need to search for alternative energy sources. Examples of areas of their practical use both in industry and in the domestic sphere of human activity are given. The advantages of their use in comparison with other types of electricity sources are noted. A practical solution for the use of thermoelectric generators at oil and fat plants is proposed